2003
DOI: 10.1074/jbc.m213253200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relations of Interactions between Na,K-ATPase, the γ Subunit, and Corticosteroid Hormone-induced Factor

Abstract: Corticosteroid hormone-induced factor (CHIF) and the ␥ subunit of the Na,K-ATPase (␥) are two members of the FXYD family whose function has been elucidated recently. CHIF and ␥ interact with the Na ؉ pump and alter its kinetic properties, in different ways, which appear to serve their specific physiological roles. Although functional interactions with the Na,K-ATPase have been clearly demonstrated, it is not known which domains and which residues interact with the ␣ and/or ␤ subunits and affect the pump kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
47
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 24 publications
9
47
0
Order By: Relevance
“…A recent study using chimeric proteins between FXYD2 and FXYD4 has revealed that the transmembrane segments of these FXYD proteins determine the opposite effect of FXYD2 and FXYD4 on the apparent Na ϩ affinity of the Na,K-ATPase (36). Together with our observations, these results suggest that not only the structural but also the functional interaction with FXYD proteins is determined by multiple interaction sites.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study using chimeric proteins between FXYD2 and FXYD4 has revealed that the transmembrane segments of these FXYD proteins determine the opposite effect of FXYD2 and FXYD4 on the apparent Na ϩ affinity of the Na,K-ATPase (36). Together with our observations, these results suggest that not only the structural but also the functional interaction with FXYD proteins is determined by multiple interaction sites.…”
Section: Discussionsupporting
confidence: 78%
“…As suggested by recent experimental evidence (33), the amino acids in FXYD proteins that are involved in the stable interaction with the Na,K-ATPase may not be the same as those involved in the functional effect, though they are also concentrated in the transmembrane domain. In our study, this could be reflected by the observation that some FXYD7 mutants affecting the N-terminal domain indeed decrease association efficiency in detergent but still produce the same functional effect on the K ϩ kinetics of Na,K-ATPase as wild type FXYD7.…”
Section: Discussionmentioning
confidence: 98%
“…The precise domain(s) or amino acids in FXYD proteins that are directly involved in the interaction with Na,K-ATPase are still unknown. Recent studies suggest that, both in FXYD2 and FXYD4, the transmembrane domain is mainly involved in the stable interaction with Na,K-ATPase (19,33) though in FXYD2 the cytoplasmic C terminus may also play a role in this process (8). In the present study, we confirm recent observations (19) that the conserved Gly 40 , which is associated with a form of renal hypomagnesemia when mutated into an arginine residue in FXYD2 (18), is involved in Na,K-ATPase-FXYD protein interaction.…”
Section: Discussionmentioning
confidence: 99%
“…For immunocytochemistry, we have used antibodies that were purified by affinity chromatography using the immunizing peptides coupled to the HiTrap N-hydroxysuccinimideactivated HP column (Amersham Biosciences). Polyclonal antibodies to the C-terminal sequences of CHIF and ␥ were described previously (24). A monoclonal antibody to a sequence near the N terminus of the ␣1 subunit of Na,K-ATPase (6H) was kindly provided by Dr. M. J. Caplan, Yale University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%